2021
DOI: 10.1108/ejim-07-2020-0275
|View full text |Cite
|
Sign up to set email alerts
|

TMT leadership ambidexterity: balancing exploration and exploitation behaviors for innovation

Abstract: PurposeThe purpose of this study is to explore balanced leadership behaviors, which exhibit ambidexterity, in a top management team (TMT) recognized for innovation and operational success.Design/methodology/approachAn action research case study was conducted in a single global organization in an industry requiring high levels of innovation. Operationalized as a balance of exploratory and exploitative behaviors, leadership ambidexterity was measured using the strategic-operational dimension of the Leadership Ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 35 publications
1
9
0
1
Order By: Relevance
“…Exploratory innovation focuses on radical changes in a firm's technological capability to discover emerging markets and satisfy new customer needs (Cho et al, 2020). It is a future-oriented activity that necessitates moving beyond current searches to pursue more experimental, risk-taking and versatile discoveries (Lawrence et al, 2022). Firms strategically seeking exploratory innovation are extending their search perspective to dilate the rigid boundaries of onsite search limitations.…”
Section: Innovation Ambidexteritymentioning
confidence: 99%
“…Exploratory innovation focuses on radical changes in a firm's technological capability to discover emerging markets and satisfy new customer needs (Cho et al, 2020). It is a future-oriented activity that necessitates moving beyond current searches to pursue more experimental, risk-taking and versatile discoveries (Lawrence et al, 2022). Firms strategically seeking exploratory innovation are extending their search perspective to dilate the rigid boundaries of onsite search limitations.…”
Section: Innovation Ambidexteritymentioning
confidence: 99%
“…A szervezeti célokat a felsővezetői csapat határozza meg. Ebből kifolyólag a felsővezetői csapatnak világossá kell tennie és modelleznie kell a megfelelő magatartást a szervezet tagjai számára, hogy éppen mire fókuszáljanak a szervezeti célok elérése érdekében (Lawrence, Tworoger, Ruppel & Yurova, 2021). A szervezeti kettős képességet a felsővezetői csapat belső folyamatai irányítják (Tushman & O'Reilly, 1996).…”
Section: A Vezetés Szerepe a Kettős Képesség Kezelésébenunclassified
“…Moreover, Zhang, Zhang, and Law (2021) found that paradoxical leadership also positively influences individual and team ambidexterity. Effective performance of top management teams also learnt to be influenced by versatility between higher degrees of exploration and exploitation (Lawrence, Tworoger, Ruppel, & Yurova, 2021).…”
mentioning
confidence: 99%